The Effects of Some External Management Factors on the Nitrogen Composition of Cattle Manure on Smallholder Farms - H. A. Markewich; A. N. Pell; D. M. Mbugua; D. J. R. Cherney; H. M. van Es; J. Lehmann (International Journal of Agronomy)
Smallholder farmers in Kenya collect manure from confined cattle housing termed zero-grazing units. Zero-grazing designs may include urine collection, though the effectiveness of these designs in improving manure N content has not been established. The manure-urine mixtures produced in these units were simulated to determine urine effects on manure N composition. Manure and manure-urine mixtures were stored for 120 days during dry and rainy seasons in Kenya. Manure-urine mixtures leached 26% of their mineral N content during the dry season, but only 12% during the rainy season. After storage, manure-urine mixtures had less organic-N and fiber-N than manure alone during the dry season (𝑃<0.01), but not during the rainy season. Results suggest that the effect of cattle urine on manure N composition is greater during dry seasons than rainy. Manure should not be stored more than 30 days to minimize N loss to leaching. Farmers may take steps to reduce N loss by controlling leaching and protecting manure from rainfall.